A Solution to the Fingering Problem of Brahms Cellos Sonata No. 1 Opus 38 and Shostakovich Cello Sonata Opus 40 - Wirayudha, Asep Hidayat (Institut Seni Indonesia Yogyakarta, 2014)
The flexibility of fingers is one main factor of responsibility on their spread ability. Considering thecello playing, the spread ability of cellists’ fingers is very important since it has a direct correlation to theirability to play the octave interval. The short- fingers cellists would find difficulties to play the octave intervalsat the first, second, third, and fourth position. Nevertheless, short-fingers are not dead-end for cellist. Thespread ability of finger, up to some extent, might be increasing through practices and exercises. It is with thisspirit that the author proposes some stratagems, which may be used to increase the spread ability of a cellist’sfingers in this section - using the octave interval problems as a case of pint. The discussion on the types andstyles of problem show that even though the octave intervals in Brahms cellos sonata No. 1 opus 38 andShostakovich cello sonata opus 40 are different in details, but fundamentally they are similar: the problemscome from the difficulty of the first and the fourth fingers to reach the proper note when the size and lengthof the fingers are limited.Solusi dari Permasalahan Fingering dalam Brahms Cellos Sonata No.1 Opus 38 danShostakovich Cello Sonata Opus 40. Kemampuan penyebaran jari pemain cello sangat penting karenamemiliki korelasi langsung dengan kemampuan mereka untuk bermain interval oktaf. Jari-jari pendekpemain cello akan menemukan kesulitan untuk bermain interval-interval oktaf di posisi pertama,kedua, ketiga, dan keempat. Namun demikian, kemampuan penyebaran jari, bisa ditingkatkan melaluipraktik dan latihan. Hal tersebut menggugah penulis untuk mengusulkan beberapa siasat baru mengenaikemampuan teknis memainkan interval dan oktav dan persoalan jarak interval dalam konteks Sonatayang dapat digunakan untuk meningkatkan kemampuan penyebaran jari seorang pemain cello. Meskipuninterval oktaf di Brahms cello sonata No 1 opus 38 dan Shostakovich cello sonata opus 40 berbeda,tetapi pada dasarnya keduanya sama: masalah datang ketika kesulitan terjadi pada jari pertama dankeempat untuk mencapai nada yang tepat ketika ukuran dan panjang jari-jari terbatas.